2015
DOI: 10.1017/s0954579414001461
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-based preventive intervention: Effectively promoting emotion knowledge and adaptive behavior among at-risk preschoolers

Abstract: Effectiveness studies of preschool social–emotional programs are needed in low-income, diverse populations to help promote the well-being of at-risk children. Following an initial program efficacy study 2 years prior, 248 culturally diverse Head Start preschool children participated in the current effectiveness trial and received either the Emotion-Based Prevention Program (EBP) or the I Can Problem Solve (ICPS) intervention. Pre- and postdata collection included direct child assessment, teacher report, parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 67 publications
1
33
0
5
Order By: Relevance
“…In a study of the Head Start REDI (REsearch‐based, Developmentally Informed), Nix, Bierman, Domitrovich, and Gill () found that preschool gains from training of social‐emotional skills was associated with improvements in several kindergarten outcomes (e.g., reading achievement, learning engagement, positive social behavior), even after controlling for concurrent preschool gains in vocabulary and emergent literacy skills. These lines of research speak to the broader recognition that social‐emotional skills and emotion regulation are important facets of early school readiness (Blair, ; Raver, ), especially for low‐income, culturally diverse populations (Finlon et al., ). The field of school psychology may consider integrating school‐based mental health into their advanced training programs so that school psychologists may be better prepared to deliver evidence‐based social‐emotional skills training alongside academic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the Head Start REDI (REsearch‐based, Developmentally Informed), Nix, Bierman, Domitrovich, and Gill () found that preschool gains from training of social‐emotional skills was associated with improvements in several kindergarten outcomes (e.g., reading achievement, learning engagement, positive social behavior), even after controlling for concurrent preschool gains in vocabulary and emergent literacy skills. These lines of research speak to the broader recognition that social‐emotional skills and emotion regulation are important facets of early school readiness (Blair, ; Raver, ), especially for low‐income, culturally diverse populations (Finlon et al., ). The field of school psychology may consider integrating school‐based mental health into their advanced training programs so that school psychologists may be better prepared to deliver evidence‐based social‐emotional skills training alongside academic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There are some exciting findings that suggest that school-based programs designed to teach skills related to emotional intelligence and competence, such as the ability to recognize and express emotions, are associated with positive outcomes across numerous domains. For example, at-risk preschoolers who received an emotion-based preventive intervention demonstrated greater gains in emotion knowledge and emotion regulation, as well as decreases in aggression, anxious/depressed behavior, and expressions of negative emotions than their peers who received a problem-solving intervention (Finlon et al, 2015;Izard et al, 2008). Of note, gains in emotion knowledge were found to mediate the effect of the intervention on emotion regulation skills, suggesting that a greater understanding of the expressions, functions, and feelings of emotions mitigated children's urge to use maladaptive coping strategies.…”
Section: Preventionmentioning
confidence: 99%
“…The BEEOS further informs the effectiveness of social-emotional interventions in promoting social and emotional development. For instance, the BEEOS revealed that an emotion-based preventive intervention led to decreases in children's negative interactions and solitary play behaviors as well as increases in positive interactions (Finlon et al, 2015;Izard et al, 2008). Last, the BEEOS can continue to inform the study of the social-emotional development of preschool children by allowing for the examination of the reciprocal relations and functions of these two independent constructs.…”
Section: Discussionmentioning
confidence: 99%
“…The type of sampling was selected because of the differences in base rates of play behaviors and emotion expressions. This procedure was then used in previous studies for targeted questions (Finlon et al, 2015;Izard et al, 2008); the current study is the first to validate the use of the whole measure.…”
Section: Development Of the Beeosmentioning
confidence: 99%
See 1 more Smart Citation